The Politics of Land Grabbing: Dispossession and Depeasantization in A Coastal Village of Bali - Bayu Adhinata (Sodality: Jurnal Sosiologi Pedesaan, 2025)
This study aims to reveal the existence of land grabbing that leads to depeasantization, taking a case study in a village on the southern coast of Tabanan District, Bali Province called Pangkung Tibah Village. In this village, investors have transferred ownership of the productive peasants' land with plans to develop an integrated tourism area. This study is interesting because most studies on agrarian affairs focusing on Bali only focus on land conversion. This study will contribute to the topic of depeasantization. The method used in this study is qualitative with a case study approach. There are three informants involved in this study: the primary informant being the Head of Pangkung Tibah Village and two first-generation peasant who were subak administrators. Data analysis in this study combines in-depth interview data collection, observation, and spatial data analysis. Triangulation of the three techniques helps researchers process data and present it into research themes. The results of this study indicate that the land grabbing process occurred in the 1990s, marked by the massive transfer of land ownership to investors. Peasant was thrown from their subsistence production methods and experienced semi-proletarian conditions. The changing culture of peasant households also contributed to depeasantization.